ETHICAL VALUES IN THE LAMIYYAT AL-ARAB: القيم الأخلاقية في لامية العرب - Muhammad Ahmad, Barkat (Institut Agama Islam Negeri Lhokseumawe, 2024)
Lamiyyat al-Arab by Al- Shanfara is an honest mirror of pre-Islamic life, reflecting its good and bad, and a pinnacle of artistic maturity. This study is a model for revealing psychological value-based phenomena in the lives of pre-Islamic people in general and Saʿālīk in particular. This paper aims to extract the most important moral values in the Lamiyyat Al-Arab, analyzing the verses of the Al-Lamiyyat related to values, while comparing them with others. The paper used the inductive, analytical, and deductive approach. The results show that Lamiyyat al-Arab expresses the values of courage, pride, kindness, generosity, and others. The life of nomadism and the dryness of nature contributed to the uniqueness of Al-Shanfara’s poetry. Al-Lamiyyat expressed a class of society, namely the Saʿālīk, through the values and morals prevailing among them. The poet expressed these values through many expressions. The poet used Bahr Al-Taweel through which he expressed the values of courage, pride, and kindness. The moral values mentioned in the Lamiya are approved by Islam and common sense. The researcher recommends more specialized studies on Lamiyyat al-Arab and other Arabic literature studies such as the artistic aspect, rhetorical, eloquence, semiotic, musical, aesthetic, and other studies.